Physico-mechanical properties of jute fiber-reinforced LDPE-based composite: effect of disaccharide (sucrose) and gamma radiation. Issue 5 (3rd May 2020) - Sahadat Hossain, Md.; Razzak, Md.; Uddin, Muhammad B.; Chowdhury, A. M. Sarwaruddin; Khan, Ruhul A.
ABSTRACT: Jute fabrics reinforced low-density polyethylene (Jute/LDPE)-based composites were prepared by compression molding technique. Jute fabrics were treated with disaccharide. The fiber content of the composites was kept constant (40% by wet). For the optimization of sucrose quantity, 0.5%, 1.0%, 2.0%, 5.0%, and 10.0% solution were prepared. For 2.0% sucrose solution, the Jute/LDPE-based composite showed the best result and the tensile strength (TS), tensile modulus (TM) and elongation at break (Eb) were 26, 940 MPa, and 18% respectively. The TS, TM and Eb values of the sucrose-treated jute/LDPE composite were low at 1% sucrose solution and the highest at 2% sucrose solution then the values decreased linearly with the increment of sucrose percentages. For 2% solution TS, TM and Eb were increased 10%, 50%, and 47% respectively with respect to non-treated composites. The impact strength(IS) was also improved about 16% with the addition of 2% sucrose. When gamma radiation (2.5, 5.0, and 7.5 KGy) was passed through the composites, the sucrose-treated composites showed relatively lower mechanical properties than the untreated composites. At 5.0 KGy gamma dose, both composites showed the best result. The water uptake property of the sucrose-treated composites was comparatively high. SEM and FT-IR were observed for both composites.